Saturated Ti-coordinated {001} facets-dependent photocatalytic water reduction over NH2-MIL-125(Ti) sheets: Observation and unraveling of facets effect - Liu, Lifang; Du, Shiwen; Xiao, Yejun; Guo, Xiangyang; Jin, Shengye; Shao, Guosheng; Zhang, Fuxiang (Applied catalysis. B, Environmental, 2023)
Facets-dependent photocatalytic H2 evolution rates of inorganic semiconductors have been well recognized, but it remains unclear for metal-organic frameworks (MOFs). Herein, we controllably prepared a series of NH2-MIL-125(Ti) MOF sheets with different ratios of {001}/{111} facets exposure, on which the photocatalytic H2 evolution rates from water are demonstrated to be almost linearly increased with enhanced proportion of {001} facets. Notably, the optimized activity of ca. 2640 μmol h-1 g-1 is by far superior to all the NH2-MIL-125(Ti)-based photocatalysts reported. The discovery of facets-dependent photocatalytic water splitting performance (i.e. facets effect) was unravelled to mainly result from their distinct charge separation abilities according to the experimental facts that the saturated six-coordinated Ti atoms (Ti6c) in the {001} facets can more efficiently accept and store the photogenerated electrons by the reduction of Ti4+ into Ti3+ with respect to the low-coordinated Ti atoms (Ti4c and Ti5c) in the {111} facets. [Display omitted] •A series of NH2-MIL-125(Ti) MOF sheets with different exposed ratios of {001}/{111} facets were controllably synthesized.•The facets dependence of the photocatalytic H2 evolution is demonstrated.•The saturated Ti6c atoms in the {001} facets are favorable for promoted charge separation with respect to the {111} facets.